Literary Reimaginings of Argentina's Independence History, Fiction, Politics - McAllister, Catriona (Liverpool University Press, 2022)
As the moment of the birth of the patria, Independence enjoys a privileged role in the historical imaginary of many Latin American nations. In Argentina as in other countries, the period has been fundamental to state discourses of nation-building and identity, lending its figures and central narratives a powerful symbolic function. It has also attracted significant literary attention, and this book offers an innovative reading of texts that provide irreverent, metafictional, or self-reflexive retellings of this foundational moment. This type of fiction is usually read through well-established frameworks on the contemporary Latin American historical novel that emphasise its destabilising of knowledge and single truths. Instead, this work foregrounds the much more immediate, concrete political points at stake when we read these texts through both their direct engagement with contemporary circumstances and the politics of the history they evoke. It therefore argues for a new approach to reading contemporary Latin American historical fiction that showcases its response to politically urgent questions.